2021
DOI: 10.1002/ceat.202100223
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Recovery of Rare Earth Elements from Red Mud

Abstract: An overview of methods used to enhance the recovery of rare earth elements (REEs) from bauxite residue or red mud (RM) is given. RM is a byproduct of the Bayer alumina production process. The composition of RM depends on the bauxite source and digestion protocol. This study aimed at developing and improving technological steps to recover REEs such as Sc, La, and Y from RM. Parameters such as leaching agent, contact time, temperature, and solid‐to‐liquid ratio were investigated to achieve optimum REE recovery f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Hydrochloric acid leaching showed the highest REE extraction rate compared with other acids. Because the different ionic radii of the REE from minerals, they do not show similar leaching rates in specific environments [ 30 , 137 , 138 ].…”
Section: Recovery Of Scandium From the Bauxite Waste (Red Mud)mentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrochloric acid leaching showed the highest REE extraction rate compared with other acids. Because the different ionic radii of the REE from minerals, they do not show similar leaching rates in specific environments [ 30 , 137 , 138 ].…”
Section: Recovery Of Scandium From the Bauxite Waste (Red Mud)mentioning
confidence: 99%
“…Based on the acid leaching and solvent extraction procedure, Li and collaborators explored the feasibility and mechanism of recovering Sc from a Sc-rich material. They observed that H 3 PO 4 outperformed HCl, H 2 SO 4 , and HNO 3 in separating Sc from impurities [ 30 ]. It was also shown that if H 3 PO 4 concentration was 6–8 mol/L and the leaching temperature was 120–140 °C, the leaching period was 60–90 min and the L/S ratio was 10–12 mL/g, the leaching of Sc approached 90%.…”
Section: Recovery Of Scandium From the Bauxite Waste (Red Mud)mentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery of alumina and ferric oxides from iron-rich red mud has been reported using the reduction sintering technique [ 112 ]. Different experiments have shown that up to 89.71% of alumina can be extracted, with a Fe recovery rate of 60.67%, under optimal conditions [ 113 ]. Zhang et al [ 114 ] investigated andradite-grossular hydrogarnet formation in the hydrothermal process with the aim of examining its effect on alumina and alkali recovery from Bayer red mud.…”
Section: Industrial Wastementioning
confidence: 99%
“…The amount of RM accumulated worldwide already exceeds 150 billion tons, and every year this amount increases by another 150 million tons [3]. At the same time, RM is an interesting source of rare earth elements (REEs) [4][5][6][7][8][9], especially scandium (Sc) which represents more than 90% of the REE value in this solid residue [10]. The Sc concentration in typical RM is about 90-120 mg kg −1 [11,12], which is five times higher than the content in the Earth's crust [13].…”
Section: Introductionmentioning
confidence: 99%